Thermomechanical behavior of functionally graded disk subjected to contact conditions - Sichani, Mohammadmehdi Shahzamanian (2010)
An analysis of thermoelastic contact problem of functionally graded (FG) rotating disk with heat source due to contact friction is presented in this thesis. Finite element method (FEM) is employed. The material properties of disk are assumed to be represented by power-law distributions in the radial direction. The inner and outer surfaces considered are metal and ceramic respectively for FG disk. Pure material is considered for the pad disk. Coulomb contact friction is assumed as the heat source. Heat source is divided into two equal parts between pad and disk which leads to thermal stresses. ANSYS parametric design language (APDL) is used to simulate the FG disk. FG disk is divided into several layers. To validate the method of division of FGM into several layers, the steady state temperature distribution of FG rotating disk has been obtained by two methods; one using APDL and the other using own developed finite element program. For own developed finite element program, triangular axisymmetric element in which the material properties vary through it is used and weighted residual method is employed. The two results compared very well. Contact status between FG disk and pure pad disk is investigated for different volume fractions. The appropriate thickness of FG disk for a full-contact status is obtained. It was found that all the areas between pad and disk are in full-contact status when the ratio of pad thickness to disk thickness is 0.66. In addition, the effect of layer number on thermoelastic results of FG disk is studied. It is seen that the thermoelastic behavior of FG disk are similar if the number of layers are bigger than 25. In addition, the influence of contact stiffness factor (Fkn ) on contact results is studied. The results show that by increasing Fkn , the contact penetration decreases and contact pressure increases. The effect of Fkn on contact total stress, contact friction stress, contact heat flux and temperature distribution are presented as well. It is observed from the thermoelastic results that the total strain due to thermomechanical load is negative for some parts of the disks, whereas the thermal strains are always positive, but by increasing the volume fraction (n) both of total strain and thermal strain increase. Moreover, it is seen that the radial stress for FG disk and full-ceramic disk are almost always positive, but for some parts of full-metal disk the radial stresses are negative. By and large, by increasing the volume fraction the value of temperature, radial displacement and absolute value of vertical displacement increase. It can be concluded from thermoelastic and contact results that volume fraction of the metal-ceramic has significant effect on the thermomechanical and contact responses of FG disks. The suitable value of n for the design of FG disk is 0.5, from the consideration of stress, temperature and contact status.